Callogenesis and somatic embryogenesis of Oryza sativa L. (cv. MARDI Siraj 297) under the influence of 2, 4-dichlorophenoxyacetic acid and kinetin - Sidek, Noorhazira; Nulit, Rosimah; Yap, Chee Kong; Yong, Christina Seok Yien; Sekeli, Rogayah; EL-Barghathi, Mariam F. (AIMS Press, 2022)
Callogenesis and embryogenesis are integral parts of many tissue culture procedures for genetic manipulation in rice. However, the efficiency of both processes is largely dependent on the media constituent especially the plant growth regulators (PGRs) due to the genotype-dependent nature of in vitro culture protocols. Therefore, this study investigates the effect of two PGRs; 2, 4-dichlorophenoxyacetic acid (2, 4-D) and kinetin (Kin) on callus growth and somatic embryogenesis of an important Malaysian rice cultivar (Oryza sativa L. cv. MARDI Siraj 297). Mature rice seeds explants were inoculated in Murashige & Skoog (MS) medium supplemented with different combinations of 2, 4-D (0 to 3.5 mg/L) and Kin (0 to 0.5 mg/L) to induce callogenesis. Parameters for callus growth such as fresh weight (FW), callus induction frequency (CIF), embryogenic callus frequency (ECF), regeneration frequency (RF), number of plantlets per callus (PPC), callus texture and callus color were observed after 35 days of inoculation. The results show that the maximum callus growth was achieved in MS medium supplemented with combination of 2.0 mg/L 2, 4-D and 0.2 mg/L Kin, represented by the highest FW (211 mg), CIF (95%), ECF (90%), RF (100%) and PPC (22 plantlets); along with friable callus texture. Low concentration of 2, 4-D (0 to 0.5 mg/L) in the presence or absence of Kin promotes root growth instead of callus, while high concentrations (above 3.0 mg/L) retard the callus formation. The embryogenic calli from this optimized PGRs combination were successfully formed shoots in MS medium supplemented with 2 mg/L BAP and 1 mg/L NAA, followed by rooting in PGRs-free MS medium. This finding provides an efficient protocol for callogenesis and somatic embryogenesis of MARDI Siraj 297, since this is the first published report regarding somatic embryogenesis induction of this cultivar.